STUDENTS’ PARTICIPATION IN INTERNATIONAL CONFERENCES AS AN INTEGRAL PART OF MEDICAL EDUCATION IN RUSSIA. ACCORDING TO THE MATERIALS OF THE XXII INTERNATIONAL STUDENT CONFERENCE - A. M. Rodionova (Сеченовский вестник, 2022)
.